Analysis of Teachers' Needs for Interactive e-Module to Train Critical Thinking Skills in the Merdeka Curriculum Era - Agusningtyas, Dwi; Erika, Farah; Qadar, Riskan (Gemilang Maju Publikasi Ilmiah (GMPI), 2024)
Integrating interactive e-module to train critical thinking skills in the Merdeka Curriculum era relies heavily on needs analysis. The Merdeka Curriculum requires a holistic and applicable approach to teaching, utilizing the STEM approach as one of its foundations to achieve this goal. The research consists of three stages: planning, data collection, analysis, and interpretation. Using a descriptive quantitative research method, the researchers collected data from 28 teachers through questionnaires, interviews with five teachers, and document studies. The research focuses on chemistry and ICT teachers who teach in SMA/MA Balikpapan. The objective is to identify students' learning difficulties with atomic structure material and nanomaterial advantages and teachers' needs for interactive e-module and readiness to use them. The study's results indicate that, according to a recent study, 77% of teachers believe that students struggle with the material, while 81% of teachers require interactive media to aid in teaching. Additionally, 83% of teachers are prepared to use interactive media and help students overcome obstacles. These findings offer valuable insights into how teachers can better facilitate STEM-based learning in the Merdeka Curriculum era. Thus, this research can contribute to developing more adaptive interactive e-module, promoting students' critical thinking skills, and supporting the vision of the Merdeka Curriculum in creating relevant and contextualized learning in the era of science and technology development.